2019
DOI: 10.1002/aic.16807
|View full text |Cite
|
Sign up to set email alerts
|

Biogas production and microbial community structure in a stable‐stage of a two‐stage anaerobic digester

Abstract: In a pilot plant under the stable-stage of the two-stage anaerobic digester, the dynamic of the archaeal, bacterial, and eukaryal community structure was studied as well as their link to performance and biogas production. An effective synergic action between microorganisms was reached since biogas production and particularly methane (CH 4) generation, were more than two-times higher in the methanogenic respect to the acidogenic bioreactor. The αand β-diversity analyses showed that dominant and rare operational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…The genus is a member of the phylum Thaumarchaeota and is generally found in geothermal environments [ 47 ]. However, recently its presence in the anaerobic digester has been reported [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…The genus is a member of the phylum Thaumarchaeota and is generally found in geothermal environments [ 47 ]. However, recently its presence in the anaerobic digester has been reported [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Carvalho [45] considered the effects of pH on bacterial communities in textile wastewater and the Illumina high-throughput sequencing results indicated that the pH significantly affected the relative abundance of Trichococcus. García-Ruíz [46] considered the effects of pH on the bacterial community structure in a black glue fermentation. The results showed a positive correlation between Intestinibacter and pH; therefore, we concluded that physicochemical properties, such as pH, TOC, NH 3 -N, NO 3 -N, TP, and TN, had a strong influence on the bacterial community structure in wastewater containing bistriazine.…”
Section: Correlation Between Bacterial Community Composition and Physicochemical Properties Of Bistriazine Ring Derivative Wastewatermentioning
confidence: 99%
“…The separation into two stages was designed in order to improve the efficiency of AD, to intensify the production of acetic acid as well as methanogenesis, and ultimately to increase the quantity of produced biogas. Hydrolysis conducted in a separate stage can be more efficient and can therefore result in lower levels of inhibiting factors in each consecutive stage of AD . In the two‐stage system, when stage 1 is separated, it can be carried out under extreme temperature and pH regimes so as to maximize its efficiency, while ensuring specific conditions for the demanding methanogenic microorganisms.…”
Section: Feedstocks Technologies and Factors Design To Intensify Bimentioning
confidence: 99%
“…The two‐stage methane fermentation process makes it possible to improve the efficiency of the process, increase amounts of produced biogas, remove VS more effectively, achieve better stability and energy recovery . In a one‐stage methane fermentation process, a problem appears due to sedimentation of heavy fractions and the appearance of foam, which can interfere with the course of the process, unlike in a two‐stage process, where methanogenesis can run more smoothly and efficiently TSAD is a promising technology to achieve better stability and improved productivity of biogas in a reactor processing highly biodegradable substrates at a higher OLR …”
Section: Feedstocks Technologies and Factors Design To Intensify Bimentioning
confidence: 99%
See 1 more Smart Citation